Double addition of phenylacetylene onto the mixed bridge phosphinito–phosphanido Pt(i) complex [(PHCy2)Pt(μ-PCy2){κ2P, O-μ-P(O)Cy2}Pt(PHCy2)](Pt–Pt). Issue 20 (6th May 2020) - Todisco, Stefano; Latronico, Mario; Gallo, Vito; Re, Nazzareno; Marrone, Alessandro; Tolbatov, Iogann; Mastrorilli, Piero
Abstract : Double addition of phenylacetylene onto the Pt(i )–Pt(i ) complex [(PHCy2 )Pt(μ-PCy2 ){κ 2 P, O -μ-P(O)Cy2 }Pt(PHCy2 )] ( Pt–Pt ) affords the η 1 -alkenyl-μ, η 1 :η 2 -alkynyl complex [(η 1 - trans -(Ph)HCCH)(PHCy2 )Pt(μ-PCy2 )(μ, η 1 :η 2 -PhCC)Pt{κ P -P(O)Cy2 }(PHCy2 )]. Abstract : The reaction of the dinuclear phosphinito bridged complex [(PHCy2 )Pt(μ-PCy2 ){κ 2 P, O -μ-P(O)Cy2 }Pt(PHCy2 )]( Pt–Pt ) (1 ) with phenylacetylene affords the η 1 -alkenyl-μ, η 1 :η 2 -alkynyl complex [(η 1 - trans -(Ph)HCCH)(PHCy2 )Pt(μ-PCy2 )(μ, η 1 :η 2 -PhCC)Pt{κ P -P(O)Cy2 }(PHCy2 )] (4 ) displaying a σ-bonded 2-phenylethenyl ligand and an alkynyl (μ-κC α :η 2 ) bridge between the platinum atoms. Complex 4 was shown to form in two steps: initially, the attack of the first molecule of phenylacetylene gives the σ-acetylide complex [(PHCy2 )(η 1 -PhCC)Pt 1 (μ-PCy2 )Pt 2 (PHCy2 ){κ P -P(OH)Cy2 }]( Pt–Pt ) (5 ) featuring an intramolecular π-type hydrogen bond between the POH and the CC triple bond; fast reaction of 5 with a second molecule of phenylacetylene results in the oxidative addition of the terminal C–H bond of the second alkyne to Pt 1 that, after rearrangements, leads to 4 . When left in solution for two weeks, complex 4 spontaneously isomerizes completely to [(PHCy2 )(η 1 - trans -(Ph)HCCH)Pt(μ-PCy2 ){κ 2 P, O -μ-P(O)Cy2 }Pt(η 1 -PhCC)(PHCy2 )] (7 ) displaying a 2-phenylethenyl ligand and a phenylethynyl group both σ-bonded to the metal. Density functional calculations at the B3LYP/LACV3P++**//DFT/LACVP* level were carried out to study the thermodynamics of the formation of all considered complexes and to trace the mechanism of formation of the observed products.